KONSTRUKSI PEMBERITAAN MEDIA TENTANG NEGARA ISLAM INDONESIA (ANALISIS FRAMING REPUBLIKA DAN KOMPAS) - - Mubarok; Made Dwi Adnjani (Jurnal Ilmiah Komunikasi Makna, 2012)
Case NII has the reach and appeal to the national and even international scale. The linkage between the interests of the state and the maker of the NII efforts being herded magnitude diverse opinions, ideas in display media pack. For media cases of kidnapping, brainwashing, and the efforts undertaken NII maker is not seen as an objective event only, but rather how it was constructed to be more meaningful to show attitude, bias or vested interest is behind the media. The media is assumed to not only bring back the reality of the news before the reader, but also include some assessment of the facts which are constructed in packaging certain attitude. The various interests in the fight in constructing the news media will cause theÂ  perspective of looking at an issue different from each other. To view the preferences of the attitude of the media framing analysis is used to highlight the problems the media strategy used to highlight and emphasize a particular fact in an event he preached.